FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH KUNJUNGAN WISATAWAN DI PROPINSI SUMATERA UTARA : FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH KUNJUNGAN WISATAWAN DI PROPINSI SUMATERA UTARA - Enita Rosmika (Juripol (Jurnal Institusi Politeknik Ganesha Medan), 2021)
Tourism Product Knowledge is regarding the general knowledge of all regions in Indonesia which includes the location of the region / geography, climate, history, politics, culture, and particularly object - attractions and facilities and attractions which support it. In this study, entitled Factors Affecting Total tourist arrivals in Sumut Province Year Period 2014 -2019. The purpose of this study was to determine the number of rooms and the dollar exchange rate partially and simultaneously inuence the number of tourist arrivals in Sumut, in order to obtain a result the number of hotel rooms inuential not evident partially on the number of tourists visiting the province of Sumut, because t smaller than t table or -1.651 <1.761 while the dollar exchange rate has a signicant effect on the number of tourists visiting the province of Sumut, because t is greater than t table or 2.236> 1.740 and Total Room and the US dollar exchange rate simultaneously or together of the number of tourists visiting Sumut Province since F count> F table or 13.288> 3.59. The magnitude of the effect of independent variables on the dependent variable simultaneously can be known from the value of the coefcient of determination (R2) is equal to 0.639. This means that both variables jointly contribute to or inuence amounted to 63.9 percent of the number of tourists visiting the province of Sumut, while the remaining 36.1 percent is inuenced by other variables that are not described in the model, such as safety, service, facilities.